Effect of Nano-Sized Poly(Butyl Acrylate) Layer Grafted from Graphene Oxide Sheets on the Compatibility and Beta-Phase Development of Poly(Vinylidene Fluoride) and Their Vibration Sensing Performance - Mrlik, Miroslav; Ilčíková, Markéta; Osička, Josef; Kutálková, Erika (International journal of molecular sciences, 2022)
In this work, graphene oxide (GO) particles were modified with a nano-sized poly(butyl acrylate) (PBA) layer to improve the hydrophobicity of the GO and improve compatibility with PVDF. The improved hydrophobicity was elucidated using contact angle investigations, and exhibit nearly 0° for neat GO and 102° for GO-PBA. Then, the neat GO and GO-PBA particles were mixed with PVDF using a twin screw laboratory extruder. It was clearly shown that nano-sized PBA layer acts as plasticizer and shifts glass transition temperature from -38.7 °C for neat PVDF to 45.2 °C for PVDF/GO-PBA. Finally, the sensitivity to the vibrations of various frequencies was performed and the piezoelectric constant in the thickness mode, d33, was calculated and its electrical load independency were confirmed. Received values of the d33 were for neat PVDF 14.7 pC/N, for PVDF/GO 20.6 pC/N and for PVDF/GO-PBA 26.2 pC/N showing significant improvement of the vibration sensing and thus providing very promising systems for structural health monitoring and data harvesting.
Keywords: grafit; poly(vinylidene fluoride); compatibility; Fluorocarbon Polymers; Graphite; Vibration; SI-ATRP; graphene oxide; vibration sensing; akryláty; dielectric properties; vibrace; Acrylates; Polyvinyls; d33; polyvinyly; fluorokarbonové polymery